Elaboración de cubetas individuales fotoactivadas para prótesis total en el laboratorio dental - Robayo Aguirre, Ivonne Aydee (2025)
The elaboration of photoactivated individual trays is a novel technique in the design and fabrication of total dental prostheses, but its implementation faces technical and methodological challenges. These trays are essential to ensure an accurate impression and optimal fit in prostheses, minimizing errors in the process. However, the lack of standardized protocols and comparative studies on photo activation methods generates inconsistencies in the results obtained in dental laboratories. Objective: To elaborate individual photoactivated trays for total prosthesis, through the systematization of professional experiences in order to perfect the technique in the dental laboratory. Materials and methods: The research was based on a qualitative approach, collecting practical experiences and reviewing academic articles, including books that deal with the elaboration of photoactivated individual trays for total prosthesis in the dental laboratory. The report addresses each stage of the practical process carried out, detailing the techniques, materials, challenges faced and procedures implemented. The critical analysis of personal experiences and partial records contributed to the preparation of a rigorous report, which not only reflects the technical development, but also the lessons learned and proposals for improvement. Results: A standardized protocol was developed for the elaboration of individual photoactivated trays, optimizing photoactivation parameters that improved anatomical fit, reduced working times and guaranteed precision. The technique supported by accessible devices such as nail lamps and dental LEDs, proved to be effective and feasible, increasing product quality, including technician and patient satisfaction. Conclusions: The systematization allowed standardizing an efficient and accessible protocol for the elaboration of photoactivated trays, improving precision and productivity. Its implementation in dental laboratories is recommended, accompanied by technical training to maximize its benefits. Key words: